GAS2L1 is a potential biomarker of circulating tumor cells in pancreatic cancer - Zhu, Lei; Kan, Kejia; Grün, Johanna L.; Hissa, Barbara; Yang, Cui; Győrffy, Balázs; Loges, Sonja; Reißfelder, Christoph; Schölch, Sebastian (Cancers, 2020)
Pancreatic cancer is a malignant disease with high mortality and a dismal prognosis. Circulating tumor cell (CTC) detection and characterization have emerged as essential techniques for early detection, prognostication, and liquid biopsy in many solid malignancies. Unfortunately, due to the low EPCAM expression in pancreatic cancer CTCs, no specific marker is available to identify and isolate this rare cell population. This study analyzed single-cell RNA sequencing profiles of pancreatic CTCs from a genetically engineered mouse model (GEMM) and pancreatic cancer patients. Through dimensionality reduction analysis, murine pancreatic CTCs were grouped into three clusters with different biological functions. CLIC4 and GAS2L1 were shown to be overexpressed in pancreatic CTCs in comparison with peripheral blood mononuclear cells (PBMCs). Further analyses of PBMCs and RNA-sequencing datasets of enriched pancreatic CTCs were used to validate the overexpression of GAS2L1 in pancreatic CTCs. A combinatorial approach using both GAS2L1 and EPCAM expression leads to an increased detection rate of CTCs in PDAC in both GEMM and patient samples. GAS2L1 is thus proposed as a novel biomarker of pancreatic cancer CTCs.